An Analysis Conflict In Movie Script Triangle Of Sadness (2022) - Oktaviani, Anggi; Moelier, Dahlia D.; Abeng, Andi Tenri (Humaniora: Journal of Linguistics, Literature, and Education, 2025)
The research aims to analyse internal and external conflicts along with their causes and impacts in the film Triangle of Sadness (2022), written by Ruben Ostlund. The analysis is conducted using the conflict theory developed by Kenney (1966). The research employs a descriptive qualitative approach, with the primary data source being the film script consisting of 98 pages. In addition, the study is supported by various relevant literature, journals, and articles. The data collection was carried out through repeated readings, note-taking of dialogues, and focused analysis based on the categories of internal conflict (man vs. self) and external conflict (man vs. man, man vs. society, man vs. nature) in accordance with the applied theory. The results indicated 15 instances of internal conflict, generally depicting the characters’ inner struggles, such as threats to self-esteem, jealousy, perceived gender role injustice, and emotional dilemmas. There were 10 instances of external conflict were identified, predominantly involving disputes between characters, particularly related to power struggles, differences in social status, and clashes of interest. The impacts of these conflicts include relationship breakdowns, social tension, decreased trust, and mental as well as emotional strain. The main causes of conflict include gender role inequality, socio-economic disparities, shifts in power dynamics, and pressures from social norms. The study reveals that Triangle of Sadness not only critiques social injustice and gender roles but also highlights how power and status can change rapidly in difficult situations, thereby influencing the characters’ identities, values, and actions.